Semi-Empirical AM1 and PM3 Calculations for Electronic Structure of Some Simple Carbonyl Compounds - Arora, Kishor (Asian Journal of Chemistry, 2010)
Carbonyl ligands are in wide use for synthetic purposes in both organic synthesis and in coordination chemistry. These are reported as stable compounds, which are in use as a ligand for synthesis of various complexes. Experimental data for some of these carbonyl molecules are available, so it prompted us to study the electronic sturcture of the compounds using semi-empirical AM1 and PM3 quantum chemical calculations. The theoretical studies were done for these carbonyl ligands to locate and confirm the site for coordination of the compounds to metal on the basis of electronic structure of these carboyl ligands.